Synthesis, structures and properties of metal–organic frameworks prepared using a semi-rigid tricarboxylate linker. Issue 4 (6th January 2022) - Rixson, Daniel; Günay Sezer, Güneş; Alp, Emre; Mahon, Mary F.; Burrows, Andrew D.
Abstract : A series of MOFs constructed from 5-((carboxymethyl)amino)isophthalic acid (H3 cmai) have been prepared and characterised, with [Cd3 (cmai)2 (H2 O)4 ]·4H2 O demonstrating loss of water in a single-crystal-to-single-crystal transformation. Abstract : The metal–organic frameworks formed from the reaction between cadmium(ii ) salts and the semi-rigid 5-((carboxymethyl)amino)isophthalic acid (H3 cmai) in water at 90 °C are dependent on the counter-ions, with [Cd2 (Hcmai)2 (H2 O)2 ]·H2 O (1 ), [Cd(Hcmai)(H2 O)2 ] (2 ) and [Cd3 (cmai)2 (H2 O)4 ]·4H2 O (3 ) forming from the nitrate, chloride and the acetate salts, respectively. Compound 3 loses both lattice and coordinated water molecules on heating to 150 °C and is converted into [Cd3 (cmai)2 ] (4 ). This reaction occurs in a single-crystal-to-single-crystal manner and was followed using variable temperature X-ray powder diffraction. The reaction of cadmium(ii ) nitrate with H3 cmai in a mixture of water and DMF afforded [Cd6 (cmai)4 (H2 O)9.75 (DMF)2.25 ]·18H2 O·1.5DMF (5 ) whereas the same reaction in water and DEF in the presence of 4, 4′-bipyridine led to [Cd3 (cmai)2 (H2 O)3 ]·6H2 O (6 ). Generally, the coordination networks containing Hcmai (1–2 ) propagate in one or two dimensions, whereas those containing cmai (3–6 ) propagate in three dimensions. Use of the first row d-block salts zinc(ii ), copper(ii ) and cobalt(ii ) nitrate resulted in compounds [M(Hcmai)(H2 O) x ] (M = Zn, x = 2 (7 ), M = Cu, x = 1.2 (8 ), M = Co, x = 2 (9 )), with 8 showing photocatalytic activity for the degradation of the dye rhodamine B. Finally, the reaction of zinc(ii ) acetate with H3 cmai in water and DEF yielded [Zn2 (cmai)(OH)(H2 O)2 ]·3H2 O (10 ). Compounds 7–10 all form two-dimensional networks.